The Piano, A Perfect Musical Instrument - Beginnings and Evolution (18th - 19th Centuries) - Tudor Brînduşa (Sciendo, 2019)
The 18th century and the beginning of the 19th century mark the emergence, development and affirmation of the piano as a complex instrument that shall take, in turns, the role of soloist instrument, claiming and being able to reach the sound variety of the orchestra, that of partner in chamber music assemblies or that of orchestra member. The emergence, improvement and qualitative performance acquisition adventure of the piano represents a fascinating history about human creativity and ingenuity serving art, beauty, sound expressivity refinement and improvement.